Praktik Corporate Social Responsibility Berbasiskan pada Etika - Putera, Asrip (Jurusan PIPS FKIP UMMY Solok, 2017)
The study was motivated by the emergence of the local community dissatisfaction against nickel mining company. Their dissatisfaction was manifested by protests and demonstrations as well as the complaints. The purpose of this study to uncover how the practice of corporate social responsibility that can give local communities. The study used a qualitative - approach fenomenology Schultz. Data were analyzed using an interactive model of Miles and Huberman. The study concludes that the values ??of ethics should be the primary consideration in the nickel mining company, active both internally and externally. All the measures taken by the management such as policies related to employees, society and the environment must always be grounded in consideration of ethical values. Ignoring the ethical values ??will cause dissatisfaction of local communities that will complicate the company in conducting. Limitations and future research, nickel mining company which is the object of research does not have a factory that the company is still short-term orientation and can vary when the company already has a plant which has been a long-term orientation, so that future studies should use informant’s company already has a factory.i